2016
DOI: 10.1007/s00436-016-5242-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for patent Toxocara infections in cats and cat owners’ attitude towards deworming

Abstract: The prevalence of and risk factors for shedding Toxocara eggs in cats older than 6 months were determined by examining 670 faecal samples collected in 4 cross-sectional studies in the Netherlands. Additionally, cat owners provided information on their attitude towards routine deworming. Samples were examined using the centrifugal sedimentation flotation method. Overall Toxocara prevalence was 7.2 %. Multivariable logistic regression analysis revealed that young age and living in rural areas were significant ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 21 publications
6
53
0
Order By: Relevance
“…Similar results were recorded in the household cats studied, but this was probably due to the fact that the majority of them also live partially outdoors. The parasitism reported in household cats in this study is in agreement with the infection rates reported in Austria, Belgium, the Netherlands, France, Hungary, Italy, Romania and Spain [6, 8, 21]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results were recorded in the household cats studied, but this was probably due to the fact that the majority of them also live partially outdoors. The parasitism reported in household cats in this study is in agreement with the infection rates reported in Austria, Belgium, the Netherlands, France, Hungary, Italy, Romania and Spain [6, 8, 21]. …”
Section: Discussionsupporting
confidence: 91%
“…since those infections were only microscopically diagnosed and as previously suggested they could either belong to T. canis or T. cati since coprophagy is not unusual for dogs and the presence of T. cati eggs in dog faeces might in fact relate to pseudoparasitism [73, 74]. The infection rates found in the present study are similar to those reported in Europe which vary from 3.5 to 34.0% for T. canis in dogs from different epidemiological environments and from 7.2 to 76.0% for T. cati in cats [8, 10, 18, 52, 7579]. The Toxocara infection was high, especially in shelter dogs and cats, as also reported before [24, 80, 81].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The most common roundworms in dogs and cats, respectively, are Toxocara canis and Toxocara cati. Most veterinary surgeons are aware of their zoonotic potential and there is some public knowledge of their effects in people, especially children [6,7]. As well as the recognised syndromes of ocular and visceral toxocarosis, meta-analyses have concluded people seropositive for Toxocara spp.…”
Section: Introductionmentioning
confidence: 99%
“…is a nematode that stands out because of its high prevalence in canids (NEVES et al, 2014), cats (NIJSSE, 2016) and human populations (MACPHERSON, 2013). The presence of Toxocara spp.…”
Section: Resultsmentioning
confidence: 99%